Work-related stress dimensions among a subsidiary company workers of Iranian oil refining and distribution company - Hatti, Mahboobeh S.; Ebrahimi, Mohammad Hossein; Gharibi, Vahid; Malakouti, Javad (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Work-related stress and its causes are among the most important issues which can seriously challenge organizational efficiency and employees' health. Different occupational environments and groups have different levels of job stress. The present study aimed to investigate relationships between job stress and its dimensions with three occupational groups (administrative, administrative-operational, and operational) among a subsidiary company workers of Iranian Oil Refining and Distribution Company. Methods The present study had descriptive-analytical and cross-sectional type and was conducted among 468 out of 503 employees (with entry condition of a year of work experience as well as an official and contractual membership) volunteered to participate in research. Data collection tools included demographic questions and job stress questionnaire as well as human resource department information to determine occupational group of employees. Descriptive statistics, statistical tests, Independent test, and one-way ANOVA in addition to SPSS 21 software were used for data analysis. Results There were significant relationships between age, education levels, work experience and smoking with mean score of job stress (P-value <0.05). Mean score of employees' job stress in operational occupation group was significantly higher than other two occupational groups (P-value=0.004), and there were significant relationships between employees' occupational group variables with five dimensions of job stress (demand, relationships and role, managerial support, and peer support) (P-value<0.05). There were not any significant relationships between other variables and job stress (P-value>0.05). Conclusions Exposure to different occupational harmful agents, facing with different safety risks, being far from family, heavy workload, and uncertain employee roles have significantly increased job stress in both operational and executive occupation groups compared to other two occupational groups; hence, there is a positive correlation between high job stress and operational jobs.